Forest landscape restoration and local stakeholders: how landowners understand restoration on the farm - Fernandes, Amanda Augusta (2023)
This master\'s dissertation deals with the study of forest landscape restoration (FLR) and the participation of local stakeholders (LS). FLR is generally defined \"as the process of restoring ecological functionality and improving human well-being across the deforested or degraded forest landscape\". FLR approaches support the involvement of different social actors in participatory decision-making processes. Between the years 2010 and 2014 numerous initiatives were proposed on a national, regional, and global scale, such as the National Plan for Native Vegetation Recovery (Planaveg) and Bonn Challenge, respectively, aiming to restore more than 350 million hectares of degraded forests by the year 2030. In 2019, the United Nations declared the decade of ecosystem restoration, between the years 2021 and 2030. Given this scenario, the need to promote biodiversity conservation and restoration, climate change mitigation, and people\'s well-being becomes evident. However, the desired gain in scale needed to achieve the global goals will ultimately depend on the decisions taken at the local level, within the farm. In Chapter 1, a general introduction to the work is presented. In Chapter 2, we conducted a bibliometric analysis survey, on a global level, to provide an overview of scientific publications on forest restoration, FLR, and local stakeholder (LS) studies, and specifically examine whether studies (1) recognized the relevance of local-level actors and (2) collected primary and/or secondary data on LS through different methods, from related publications since 2000. It was observed that, only 50% (99 records) of the studies recognized the relevance of local level actors and also collected primary and/or secondary data through different methods. In Chapter 3, we determined the social-ecological factors that led different-sized farms (small, medium, and large) to decrease (deforestation), maintain (conservation) and/or increase (natural regeneration and/or forest restoration) native forest cover (NFC) area on their farms in the past 35 years, and the perceived benefits or disadvantages of NFC. In this chapter, it was observed that i) small, medium and large scale farmers have reported reasons to decrease, increase and maintain NFC within their properties, with large farmers reporting more reasons to decrease; ii) the perception of farmers on benefits provided by native forest differs among farmers, with small and medium farmers perceiving more benefits and; (iii) farmers and farms characteristics affect the benefits perceived. In the final topic, we present a general conclusion of the dissertation.